"DIscrepancia del eje longitudinal coronal y radicular en incisivos laterales superiores Piura 2016." - Uribe Rocca, Edith del Rosario (2017)
ABSTRACT The purpose of this study is to determine the prevalence of the discrepancy in the root-crown longitudinal axis in the Upper lateral incisors. The study was made in Piura City in 2016. It was requested Panoramic x-rays from a radiological center, with the exclusion criteria and elimination and the sample was 192 x-rays of patients between 14 and 30 years old. The traces of the coronal and radicular axis were performed to the right and left lateral incisors in a virtual way; the strokes were made by a specialist after developing the self-calibration test. The discrepancy of the crown-root angulation was 81% with a media of 3.68° , most of them presented a mesial inclination and its media was 2.99°. Only 19% of the patients had no discrepancy between the coronal longitudinal axis and the root longitudinal axis in the right upper lateral incisor. The femail presented more prevalence in the desviation crown-root with a media of 3.01°, there was nosignificant difference between both hemiarcades.